2010
DOI: 10.1386/jaah.1.2.193_1
|View full text |Cite
|
Sign up to set email alerts
|

The experience of acting: A synthesis of concepts and a clinical vignette

Abstract: This article illuminates the experience of acting through a synthesis of concepts from therapy, arts, and philosophy. Through the lens of performance theory, the author first addresses the difference between acting in the context of formal theatrical acting and acting in the context of drama-based psychotherapy. By applying Sartrean concepts the author characterizes the experience of witnessing in the case of tangible and permanent works of art versus witnessing in the case of embodied and ephemeral performing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The concept of presence is also used in the arts, where it is described as an “indefinable intangible quality” (Stanislavskij & Hapgood, 2004) that is characterised by reduced fatigue, “flow,” out‐of‐body sensations, detachment, control and readiness, awareness and openness (Atkins, 1990; Orkibi, 2010). In acting, presence is the moment when the actor and audience are fully and totally in communion, consumed by the moment, and fully present together (Zarrilli & Hulton, 2009).…”
Section: Grounded Theory Case Examplementioning
confidence: 99%
“…The concept of presence is also used in the arts, where it is described as an “indefinable intangible quality” (Stanislavskij & Hapgood, 2004) that is characterised by reduced fatigue, “flow,” out‐of‐body sensations, detachment, control and readiness, awareness and openness (Atkins, 1990; Orkibi, 2010). In acting, presence is the moment when the actor and audience are fully and totally in communion, consumed by the moment, and fully present together (Zarrilli & Hulton, 2009).…”
Section: Grounded Theory Case Examplementioning
confidence: 99%
“…What this study showed us when their goal is to achieve unity within a group, humor enabled individuals to selectively elicit empathy within their group, allowing them to be more personal with them. Oring (1992) illustrated the intersection of humor, laughter and the comic, describing it as discovery between the performer and the audience through laughter. In order for that to happen the comic -or sender -must be willing to give their point of view.…”
Section: Comic's Identity: a Vulnerable Expressionmentioning
confidence: 99%